Hell fest [videorecording (DVD)] - Forsyth, Amy, 1995-; Edwards, Reign; Taylor-Klaus, Bex (Lions Gate Home Entertainment, 2019)
A masked serial killer turns a horror-themed amusement park into his own personal playground, terrorizing a group of friends while the rest of the patrons believe that it is all part of the show.